Complete Hearing Recovery in Sudden Sensorineural Hearing Loss with Type 2 Diabetes Mellitus and Steroid-Aggravated Hyperglycaemia: A Case Report - Ni Made Pasmiati Setyaningsih; Ni Putu Oktaviani Rinika Pranitasari (Greenation Publisher & Yayasan Global Research National, 2026)
Sudden sensorineural hearing loss (SSNHL) is an otologic emergency defined as a hearing decline of at least 30 dB across three contiguous frequencies within 72 hours. Type 2 diabetes mellitus (T2DM) is a recognised risk factor and a predictor of poorer recovery, yet high-dose corticosteroid remains first-line therapy, creating a therapeutic dilemma. A 56-year-old woman with severely uncontrolled T2DM (HbA1c above 14%) and hypercholesterolaemia presented two days after sudden right-sided hearing loss. Audiometry confirmed moderate-to-severe SSNHL of the right ear. She received intravenous methylprednisolone tapered over 15 days, five sessions of hyperbaric oxygen therapy, statin therapy, and endocrinology-guided basal-bolus insulin. Hearing thresholds returned to normal by treatment day seven and remained normal at day twelve, meeting complete recovery by modified Siegel's criteria. Capillary glucose exceeded the glucometer limit of 500 mg/dL on four occasions, highest measured value 496 mg/dL. Hyperglycaemia was managed by insulin intensification without reducing or discontinuing corticosteroid, and no clinical hyperglycaemic crisis was documented. Causal attribution of recovery to treatment cannot be established from a single case because several favourable prognostic factors were present. Full-dose corticosteroid appears feasible in severely uncontrolled T2DM when structured glucose monitoring and endocrinology collaboration are available.